Kød-brød og blod-vin - Enggaard, Nete (Dansk Teologisk Tidsskrift, 2008)
The article questions the metaphorical interpretation of Lutheran theology arguing that metaphor and language has been reduced to a surrogate for a metaphysically conceived notion of being as a static and eternal entity. In the light of Cathrine Malabou’s notion of plasticity, explosive and so far neglected ontological implications of Luther’s sacramental metaphors are brought to light: Luther’s paradox metaphors rest upon his interpretation of communicatio idiomatum and the doctrine of the real presence as a structure of difference and temporality. This suggests that the sacrament in Lutheran thought has implications for the concept of God itself. A postmodern reading of Luther’s late confession Vom Abendmahl Christi calls for a renewed theological interpretation of concepts such as metaphor, temporality, future and God.